Neonatal Brain Tumors: A Review - Bodeliwala, Shaam; Kumar, Vikas; Singh, Daljit (Journal of Neonatal Surgery, 2017)
Brain tumors in neonatal age group is uncommon comparing with older children and adults. In older children brain tumors are commonly infratentorial, where as in neonates, they are supratentorial. Though extracranial tumors are commoner in neonates, brain tumors cause 5-20% deaths approximately. We are presenting a review on brain tumors in neonates.